Beyond informational privacy: Freedom of choice and identity in the algorithmic profiling era - Tiribelli, Simona (Itinerari, 2023)
The protection of individual identity is one of the most prominent and discussed issues within the debate in the field of ethics of artificial intelligence (AI) and ethics of algorithms specifically. However, thus far, the debate has mainly focused on the threats raised by AI and algorithm-based ICTs to personal identity in terms of informational privacy infringements, while no specific contribution has been developed on their impact on individual moral identity and, in particular, on our freedom to develop an authentic moral identity. This paper aims at filling this gap. To do so, by drawing on moral philosophy, we pursue an ethical inquiry and show how algorithm-based ICTs can negatively affect the preconditions of our freedom of choice and action and, by doing so, erode over time our freedom to develop authentic moral identities. Finally, we pinpoint key ethical criteria that acknowledge, but also go beyond existing informational privacy-preserving solutions, in order to design algorithm-based ICTs that can ensure at least at a minimum threshold the protection of our freedom to choose, act, and therefore, to develop authentic moral identity in our hyper-profiled onlife environments.